Contra Semi*$δ$-Continuous Functions in Topological Spaces - S. Pious Missier; C. Reena; G. Mahadevan (International Journal of Mathematics And its Applications, 2017)
In this paper we define contra-semi*$δ$-continuous, contra-semi*$δ$-irresolute, semi*$δ$-open and semi*$δ$-closed functions and investigate their properties.